My Remembers A Black Sharecropper's Recollections of the Depression - Stimpson, Eddie (University of North Texas Press, 1999)
"I grow up a dirt farmer and retired a dirt farmer. Never got rich and didn't want to be. My childhood stomping ground is now concrete, stores and houses. I remember the good times and bad. It was not the money we made but how to stretch that last dime. It was not the wind, rain or snow. It was about the love that flow. It was not the hot sunshine nor the clouds that hung low. It was the grace of God that help us swang that hoe. I want my grandchildren to understand. My grands, your grands and their grands." In 1929, near Plano, Texas, Eddie Stimpson, Jr., weighing 15-1/2 pounds, was born to a 19-year-old father and a 15-year-old mother. The boy, his two sisters and mother all "grew up together," with the father sharecropping along the old Preston Road, the route used by many freedmen trying to escape Texas after the Civil War. His childhood was void of luxuries, but full of country pleasures. The editors have retained the simplicity of Stimpson's folk speech and spelling patterns, allowing the good-natured humility and wisdom of his personality to shine through the narrative. "Tough time never last," he writes, "but tough people all way do." The details of ordinary family life and community survival include descriptions of cooking, farming, gambling, visiting, playing, doctoring, hunting, bootlegging, and picking cotton, as well as going to school, to church, to funerals, to weddings, to Juneteenth celebrations. This book will be of extraordinary value to folklorists, historians, sociologists, and anyone enjoying a good story. "My spelling is bad, my hand writing is bad, and my language is bad," Stimpson writes. "But my remembers is still in tack."